Are good intentions enough? The role of the policy implementer during educational reform. Issue 1 (2nd January 2019) - Curran, Helen
ABSTRACT: Nationally the educational landscape is changing and it could be argued that reform is taking place at an unprecedented rate. Associated with educational reform is the introduction of new policy, including statutory guidance. This article seeks to consider policy implementation in schools, specifically through the lens of the policy actor typology (Ball et al., 2012 ). The article focuses on the introduction of the SEND reforms and deliberates the policy actor roles the SENCO, as a key implementer, could be seen to assume. Additionally, the article queries the potential barriers which may prevent the implementation of policy as originally conceived as well as the potential outcome of unintended consequences, ultimately asking the question, 'Are good intentions enough?'